Sestava in število lokalov v starem mestnem jedru Slovenj Gradca med letoma 1945 in 2000 - Krajnc, Dimitrij (Geografski vestnik, 2001)
The article is about premises in old town centre of Slovenj Gradec between 1945 and 2000. It's presented their numerous growths, spread in place and changes in their structure. At the end of the article are presented major reasons, which caused those changes.
Keywords: geografija naselij; mesta; mestna jedra; storitve; Slovenj Gradec